SIRT6 in Senescence and Aging-Related Cardiovascular Diseases - Li, Xiaokang; Liu, Lin; Li, Tian; Liu, Manling; Wang, Yishi; Ma, Heng; Mu, Nan; Wang, Haiyan (Frontiers in Cell and Developmental Biology, 2021)
SIRT6 belongs to the nicotinamide adenine dinucleotide (NAD+)-dependent deacetylases and has established diverse roles in aging, metabolism and disease. Its function is similar to the Silent Information Regulator 2 (SIR2), which prolongs lifespan and regulates genomic stability, telomere integrity, transcription, and DNA repair. It has been demonstrated that increasing the sirtuin level through genetic manipulation extends the lifespan of yeast, nematodes and flies. Deficiency of SIRT6 induces chronic inflammation, autophagy disorder and telomere instability. Also, these cellular processes can lead to the occurrence and progression of cardiovascular diseases (CVDs), such as atherosclerosis, hypertrophic cardiomyopathy and heart failure. Herein, we discuss the implications of SIRT6 regulates multiple cellular processes in cell senescence and aging-related CVDs, and we summarize clinical application of SIRT6 agonists and possible therapeutic interventions in aging-related CVDs.